Income and Education as the Determinants of Anti-Corruption Attitudes: Evidence from Indonesia - Anita K. Zonebia; Arief Anshory Yusuf; Heriyaldi Heriyaldi (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2019)
A higher level of corruption is found to be associated with a lower level of income in most cross-country studies. However, at any given income level, education can also be a very important determinant of the level of corruption, and failing to include education may bias or overestimate the importance of income. We estimated an empirical model of an individual’s attitude toward anti-corruption using a large sample of 9,020 individuals who represent the Indonesian population and found that the effect of income (measured by expenditure) is either weakened or eliminated when we controlled for the level of education. The effect of education is also found to exhibit a nonlinear pattern, which implies that investing in education will have increasing returns in the form of an anti-corruption attitude. This finding supports the view that increasing access to education is an effective measure to reduce corruption norms, particularly in developing countries.